Effects of ascorbic acid on the germination and vigour of cowpea seeds under water stress - Nunes, Luma Rayane; Pinheiro, Paloma; Silva, João; Dutra, Alek (Revista Ciência Agronômica, 2020)
Water is one of the most compromising factors in the germination and initial growth of seedlings, where its restriction causes a reduction in the water potential of cells in addition to causing oxidative stress. Ascorbic acid (AsA) is known to protect organelles and cells against the accumulation of ROS. The aim of this work was to study the effects of ascorbic acid on the conditioning of cowpea seeds subjected to water stress. The seeds of the BRS Marataoã and Setentão genotypes were conditioned at a concentration of 0.0 (control), 0.25, 0.50, 0.75 and 1.00 mM AsA, and sown on paper rolls (Germitest®) moistened with mannitol solution at a potential of 0.0 (control), -0.3, -0.6, -0.9 and -1.2 MPa, and stored in a germination chamber (BOD) at 25 ºC. The experiment was conducted in a completely randomised design, in a 2×5×5 factorial scheme, with four replications of 50 seeds per treatment. The variables under analysis were percentage germination, first germination count, germination speed index, shoot and root length, total seedling dry weight and electrolyte leakage in the leaves and roots. Conditioning the seeds with ascorbic acid at a concentration of 0.50 mM for the BRS Marataoã genotype and 0.75 mM for the Setentão genotype, enabled the development of more vigorous seedlings and a reduction in the damage caused to the membranes by oxidative stress, both in the absence of a water deficit and at the osmotic potentials under test, including at the lowest potential.